Big Data-Based Internal Control and its Impact on Improving Financial Reporting Quality - Jinan Abed Khaji (International Journal on Economics, Finance and Sustainable Development, 2026)
Contemporary work environments face escalating challenges due to the massive and enormous volumes of financial and operational data produced by economic units, which has led to making Big Data technologies one of the key tools for developing internal control systems and improving the quality of financial reports. The current research aims to study the role of Big Data-based internal control systems in enhancing the credibility, accuracy, and transparency of financial reports in Iraqi economic units. This is achieved by developing a theoretical framework that links internal control practices with advanced data analysis tools, and then practically testing this framework through a targeted questionnaire directed at a sample of employees in internal control departments, financial accounting, and risk management. The research concludes that integrating Big Data tools into the design of internal control for economic units is crucial to mitigate financial errors and detect manipulation early, which strengthens investor confidence and achieves a competitive advantage for economic units. The findings of this research contribute to bridging the knowledge gap, whether at the local or regional level, by demonstrating the potential of investing in digital transformation to develop internal control environments and improve the quality of financial reports in Iraq.